estión de los activos corrientes del año 2017-2018 de la empresa RAFSAN S.A. - Mosquera Tapia, Elisa Lisbeth (2020)
RAFSAN has been one of the intermediary companies between farmers and industrial companies, one of the oldest in the Windows canton, the corn capital of Ecuador, the company's economic activity is the wholesale of cereals (grains), it is applied the deductive method in the case study, since the current assets of the statement of financial position for the year 2017-2018 were analyzed through vertical analysis, horizontal analysis and the financial ratios to measure the ability of the company to generate liquidity and the efficiency of using said resources, which affects the result for the period, in order for the company to implement strategies making the best decision by the shareholders, regarding the resources and liquidity of the current assets it owns, and its You will improve the results of the period allowing the company to obtain profitability.